The Use of Herzberg's Two-Factor Analysis To Formulate An Employee Incentive Program on The Example of A State Administration Office In Poland - Urszula BALON; Mariusz GIEMZA (Communications of International Proceedings, 2022)
What is important for the organization is a person who reliably performs his duties, is conscientious, effective in action and brings benefits to the organization. An employee who performs his duties well should be competent, committed and motivated. There are many studies and classifications of employees' motivating factors in the literature. One of the theories dealing with the motivating factors of employees is Herzberg's two-factor theory, which distinguished two groups of factors: hygiene factors, which lead to dissatisfaction, and motivators, which contribute to the employee's satisfaction with the performed duties. The aim of the article is to present the application of the Herzberg’s two-factor method to determine the factors influencing the motivation of employees of the state administration office in Poland. According to the research carried out by the authors, employees of public offices include among the most motivating factors: good relations at work with both colleagues and management, stability of employment, and additional remuneration. According to Herzberg's theory, these factors belong to the factors of mental hygiene and do not have a motivating effect. On the other hand, typical motivators according to Herzberg, which the employees of the office also pay attention to, are their own job satisfaction, personal development and the possibility of using training financed by the employer. However, these factors were stated as less important by the respondents. Based on the knowledge of the factors that are important for employees, managers should develop an incentive system adjusted to employees, which will have a positive impact on the duties performed by employees, and will positively affect the development of the organization.
Keywords: Herzberg`s two factors theory; motivation; state administration office